The effects of inhaled enamel and dentin dust in lungs of white mice A histopathologic study - Hakym, Fowzia K.; Mercado, Marie Donna F.; Gervasio, Natividad (Adviser).
Ten white mice, five male and five female approximately three weeks old were obtained for this study to determine if inhaled enamel and dentin dust can induce pathologic changes in their lung tissue. The results from the study are rather non-specific and it is not possible to form any opinion based on this. Although some of the pathologic changes may have been due to the exposure to the enamel and dentin dust, not enough evidence present to make any definite conclusion.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Occupational exposure; Pneumoconiosis